Assessing the contribution of climate change on tropical cyclones related to loss and damage in southern Africa: a case study of tropical cyclones in southern Malawi - Joshua, Miriam Dalitso Kalanda; Kasei, Raymond Abudu; Wamukoya, George (Frontiers in Water, 2026)
This study synthesizes peer-reviewed literature and government reports to examine the relationship between climate change and the frequency, occurrence, and intensity of tropical cyclones in southern Malawi. The research employs a mixed-methods approach, combining spatial mapping, literature synthesis, and trend analysis of cyclone data from the past three decades. It also analyzes rainfall data from nine meteorological stations using the Standardized Precipitation Index (SPI) and conducts stakeholder interviews across four districts. Using literature review of peer-reviewed literature and government documents, this study assessed the link between climate change and the occurrence, frequency, and magnitude of tropical cyclones that lead to Loss and damage in several areas, including various types of physical infrastructure, agriculture, and food security in Africa. The study focuses on Southern Africa, using Malawi as a case study. It examines the occurrence and frequency of tropical cyclones in the Southern region over the past 30 years. Specifically, the study aims to: (i) Analyze trends of tropical cyclones and related temperature and extreme rainfall events, including floods, for the past three decades, and (ii) Map areas affected by Tropical cyclones and related extreme rainfall events over the past 30 years. Findings reveal an increasing trend in tropical cyclone occurrences since the 2000s, with particularly intense events such as those in 2015, 2019, and 2023 coinciding with La Niña conditions. Statistical analysis using Mann-Kendall trend tests and Pearson correlations confirms significant upward trends in both cyclone frequency (Tau = 0.29, p < 0.05) and rainfall anomalies (r = 0.51, p < 0.01). The study results show an increasing occurrence of Tropical cyclones from the 2000s. These findings demonstrate correlations between increased cyclone activity and climate change indicators, consistent with established attribution studies but requiring additional multivariable climate modeling for definitive causal attribution, reinforcing the need to prioritize agricultural resilience within the Loss and Damage framework under the UNFCCC. The increasing trends in cyclone frequency and intensity show correlations with climate change patterns and align with established climate projections. However, definitively establishing direct causal attribution requires comprehensive climate modeling, which is beyond the scope of this study. These observed trends are consistent with regional attribution studies, suggesting that management of losses and damages in agriculture deserves special attention within the Loss and Damage framework.